(untitled) (Academicia Globe: Inderscience Research, 2023)
In the content of the pedagogical process aimed at developing the pronunciation and speech of elementary school students through folklore, it is a complex interactive quality of the student, personal qualities, self-work and self-speech. represents abilities such as being able to demonstrate.